Relationships Between College Students’ Control-Value Appraisals of English Learning, Achievement Emotions, and Empowerment - Jian Wang; Xiaohong Zhang (Vision: Journal for Language and Foreign Language Learning, 2024)
Language learning involves cognitive and non-cognitive factors. Recent research has shifted focus from cognitive outcomes to emotional factors, influenced by positive psychology and an "affective turn" in second language studies. In light of this, the current study preliminarily examined the interrelationships between tertiary-level English learners’ control-value appraisals of English learning, academic emotions (i.e., enjoyment and boredom), and empowerment. A study of 289 non-English major students in southwest China used convenience sampling and quantitative questionnaires to assess their control-value appraisals of English learning, boredom, enjoyment, and empowerment. The findings indicate that learners’ enjoyment and value appraisals of English learning were at an upper-middle level, while control appraisal and empowerment were at a moderate level. Boredom, however, was rated at a lower middle level. Furthermore, there were significant correlations between these variables. Overall, control and value appraisals played a substantial role in predicting learners’ achievement emotions and empowerment. The affective aspects of language learners are essential elements that potentially shape their learning processes and outcomes. This study suggests that to empower students in their language learning journey, teachers should help them recognize the meaningfulness of language learning, bolster their self-efficacy, and create an engaging and enjoyable learning environment.